A Study on Everyone Has a Story by Amitav Ghosh (International Journal of Food and Nutritional Sciences, 2022)
This work portraits amitav ghosh novel that address the underlying theme everyone has a story. The work also addresses the various dialects used in the Indian novel literature and compares the same with the work of amitav ghosh. In general the indian English has its own dialects that reflects in every novel and in this work address the dialect used by amitav ghosh on the same to represent the concepts of the above mentioned dialects